Determination of Thermal Resistance of Semiconductor Lasers from Parameters Measured in Pulsed Regime - Pernas, R.; Abelenda, A.; Sánchez, M. (Revista Cubana de Física; Vol 27 No 2B (2010), 2010)
We obtain the thermal resistance (Rt) and the maximum operating temperature of different semiconductor lasers using parameters measured in pulsed regime. A method previously developed in our laboratory was used to which are added, the uncertainty budget and a criterion to decide the Rt value to be reported. The results obtained in this way were found in good agreement with reported values obtained by other methods. Results for GaInNAs lasers are the first reported values of the thermal resistance in this material. Although the characteristic temperature in these devices is higher that those of GaInAsP, the thermal resistance is similar indicating that further improvements are still required to appreciate the full potential of dilute nitride devices.